Safe and Secure Software Reuse 13th International Conference on Software Reuse, ICSR 2013, Pisa, June 18-20. Proceedings - Favaro, John.; Morisio, Maurizio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 13th International Conference on Safe and Secure Software Reuse, ICSR 2013, held in Pisa, Italy, in June 2013. The 27 papers (18 full and 9 short papers) presented were carefully reviewed and selected from various submissions. The papers are organized in topical sections on feature modeling and variability analysis; reuse and testing; architecture and reuse; analysis for reuse; reuse and patterns, short papers, emerging ideas and trends.
Feature modeling and variability analysis -- Reuse and testing -- Architecture and reuse -- Analysis for reuse -- Reuse and patterns -- Short papers -- Emerging ideas and trends.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering; Programming Techniques; Programming Languages, Compilers, Interpreters; Software Engineering/Programming and Operating Systems; Models and Principles